A REVIEW OF CLINICAL LEGAL EDUCATION’S (CLE) EXPERIENCE IN UNIVERSITI SAINS ISLAM MALAYSIA - Che Musa, Norsuhaida; Nawi, Nor Fadzlina (Malaysian Journal of Syariah and Law, 2021)
Various research has given valuable insights into the positive role of Clinical Legal Education (CLE). However, there is a dearth of empirical data reviewing the set-up of CLE in public law schools in Malaysia and assessing its role as a teaching and learning strategy in legal education. This paper summarises the development and structure of the Faculty of Syariah and Law's Legal Clinic pilot initiative at the Universiti Sains Islam Malaysia (USIM). It assesses the impacts of the initiative on students' learning experience. The assessment involved a content analysis of written feedback given by a batch of pioneer students selected to join the FSU Legal Clinics pilot project in 2019. The findings indicated that the students believe exposure to the legal clinic increases their comprehension of the law's application and provides awareness of the professional skills and values involved in the legal profession. The sample is small, and the findings are preliminary. However, it is hoped that the results will inform legal curriculum developers of the benefits that law students derived from their clinical experience and provide a basis for further research into formally including clinical legal education in the FSU legal curriculum. This paper also advocates that although setting up, planning and organising activities for a successful legal clinic involved a great deal of preparation, it would benefit students and be integral to teaching and learning strategy in legal education in FSU USIM.